Influence of current density on crystalline structure and magnetic properties of electrodeposited Co-rich CoNiW alloys - Sakita, A. M P [UNESP]; Passamani, E. C.; Kumar, H.; Cornejo, D. R.; Fugivara, Cecilio Sadao [UNESP]; Noce, R. D. [UNESP]; Benedetti, Assis Vicente [UNESP] (My University, 2013)
The influence of current density, at the interval 5-100 mA cm-2, on the structural and magnetic properties of electrodeposited (Co 100-xNix)100-yWy alloys (x = 23-33.5 at. % Ni, y = 1.7-7.3 at. % W) was studied from a glycine-containing bath. W-content decreases with the increase of the current density magnitude. X-ray data have shown stabilization of hexagonal close packed, face centered cubic or a mixture of these structures by modulating the applied cathodic current density, for values lower than 50 mA cm-2. Two structural phase transitions were observed: one from hexagonal close packed to face centered cubic structural transition occurring for a current density of 20 mA cm -2, and another one, from cubic crystalline phase to amorphous state, which happens for values higher than 50 mA cm-2. These structural phase transitions seem to be associated with the W-content as well as average crystalline grain sizes that reduce with increasing the current density value. The grain size effect may explain the face centered cubic stabilization in Co-rich CoNiW alloys, which was initially assumed to be basically due to H-adsorption/incorporation. Magnetic properties of Co-rich CoNiW alloys are strongly modified by the current density value; as a result of the changes on the W-content and their structural properties© 2013 Elsevier B.V. All rights reserved.
Keywords: Alloys; Chemical synthesis; Electron microscopy; Magnetic materials; Magnetic properties; Cathodic current density; Crystalline grain size; Crystalline structure; Face-centered cubic; Hexagonal close packed; Structural and magnetic properties; Structural phase transition; Structural transitions; Alloying; Amino acids; Cerium alloys; Crystalline materials; Electrodeposition; Grain size and shape; Nickel; Stabilization; Synthesis (chemical); Current density